Embedded physical‐layer authentication in cognitive radio requires efficient low‐rate channel coding schemes. Issue 3 (1st February 2017) - Wu, Xiaofu
Abstract : In this study, the author investigates the practical limitation of the recently proposed embedded cryptographic signature authentication scheme at the physical layer. By employing the log‐likelihood ratio of a tag bit and its approximation, the author shows that the equivalent authentication channel observed by the secondary receiver can be viewed as a binary‐input additive white Gaussian noise channel. Then, the sphere‐packing lower bound can be employed to show the transmission capability for practical finite‐length authentication tags. To achieve the same effective coverage area for both the primary and secondary receivers, it essentially requires efficient low‐rate channel coding schemes with near sphere‐packing‐bound performance at the secondary receiver, which contrasts sharply with the pessimistic conclusion of Jiang et al.